The traditional hunting on Greater Green Leafbird (Chloropsis sonnerati) in East Java: A vulnerable situation for vulnerable bird - Agung S. Kurnianto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2017)
Greater Green Leafbird (GGL) Chloropsis sonnerati is one of the favorite songbird in Indonesia and live harmoniously among local people. However the increasing human needs creates a vulnerable situation, both to socio-economic and bird sustainability. This study aims to reveal the GGL tradi-tional hunting method in two villages within the national park. In addition, this study also aims to reveal the trading plot from the initial supply to the local traders and the fluctuation of GGL population in their natural habitat. We conducted two approaches: an explorative interview on bird traders in Malang, Jember, and Banyuwangi, and a deep interview on the national park rangers, society, and bird hunters. Local people generally use two methods for GGL hunting. Pikat method, was used to catch specific birds that mostly live on trees. The other method, net method, was not widely used by the traditional hunter. Population of GGL was considered as abundant in the past, when the demand was low and the hunting activity only conducted seasonally using pulot method. The high of demand, modernization of method, and regeneration of hunters shifted the sustainable harvest into exploitation. During 2001-2003, the trend of hunting began to decline the GGL population in nature.